(untitled) (SAINTEKBU, 2016)
Application of artificial neural network software ( ANN ) has been implemented for predicting many thing and replace the conventional ways of predicting method using linear regression. Back Propagation algorithm can be used to reach the result of the program that can predict the telephone exchange health grade according to the data that has been recorded before. By predicting each parameter that has correlation to the telephone exchange health grade, we can predict the telephone exchange health grade in the next period. Kata kunci : jaringan syaraf tiruan, propagasi balik, nilai kesehatan sentral.